#TITLE_ALTERNATIVE# - LESMANA (NIM : 12212078), ANDREW
The production rate of a well that penetrates a heavy oil reservoir increases considerably if, prior to production, the formation around the borehole is heated by injecting a slug of steam through the well. Cyclic steam stimulation has been the most frequent and successful process applied to thermal recovery programs. One cyclic steam stimulation consist of injection process, soaking process, and production process. As the heat gradually dissipates during production, high production rates can only be sustained if additional steam are occasionally injected to reservoir. Since there is no oil production during the injection and soaking period, there is a suggestion to minimize the frequency of steaming and increase the length of the production time. But on the other hand, because of the heat gradually dissipates during production, there is another suggestion to increasing steaming frequency and reducing the length of the production time. Combination of optimum production and injection period for cyclic steam process to maximize the results in productivity during each cycle. The problem become more complex when steam quality and temperature of injection steam are considered. If we want to solve the problems with all consideration, we need a lot of time and effort. The objective of this research is to find the best solution using genetic algorithm for cyclic steam well.